Health and cleanliness : a text book for teachers - Green, George H. (George Henry), 1881- ; Buchan, G. F.; Muir, W. A. (London : Health and Cleanliness Council)
1938-03 1938 1930s 69 pages : illustrations FOREWORD TO THE SIXTH EDITION BY GEORGE F. BUCHAN, M.D., F.R.C.P., D.P.H., PRESIDENT, HEALTH AND CLEANLINESS COUNCIL CLEANLINESS may properly be considered as the fundamental basis of all hygienic measures and sanitary reforms. This book is issued as an aid to teachers in their endeavours to inculcate habits of cleanliness amongst their pupils. It was first published in 1928, and many have been the revisions and reprints since. The great popularity of the book shows that it is meeting a real need. The authors are men of eminence in their respective spheres of health and education, and the syllabuses for the groups of lessons have been carefully planned so that the teacher may be able to demonstrate the important relationship of cleanliness to health in a systematic, simple and effective manner. The textbook has the wholehearted support and approval of the Health and Cleanliness Council, and this edition is heartily commended to teachers in the hope that it will be found sound, helpful and instructive. March, 1938. [Logo] It's Cleanliness that counts 177/5/8/3